2018
DOI: 10.1186/s12889-018-5505-7
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity in populations in the vicinity of coal mining: a systematic review

Abstract: BackgroundEvidence of the association of coal mining with health outcomes such as increased mortality and morbidity in the general population has been provided by epidemiological studies in the last 25 years. Given the diverse sources of data included to investigate different health outcomes in the exposed populations, the International Classification of Diseases (ICD) can be used as a single classification standard to compare the findings of studies conducted in different socioeconomic and geographic contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 68 publications
2
43
0
3
Order By: Relevance
“…In addition to miners, air pollution from mining activities, including extraction, processing, and bulk transport, impacts the health of the community at large [10,37,38]. Our analysis confirmed that PM10 exposure levels were significantly elevated in mining communities relative to urban or rural nonmining communities.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…In addition to miners, air pollution from mining activities, including extraction, processing, and bulk transport, impacts the health of the community at large [10,37,38]. Our analysis confirmed that PM10 exposure levels were significantly elevated in mining communities relative to urban or rural nonmining communities.…”
Section: Discussionsupporting
confidence: 65%
“…Air monitoring stations in coal mining areas are scarce; in Queensland and New South Wales, for example, there are 19 such monitors compared to 45 in nonmining urban areas. No direct health assessments were made in this study, although considerable additional evidence indicates that coal mining adversely impacts public health [10,43].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown clear links between coal mining and respiratory diseases ( Perret et al, 2017 ; Laney and Weissman, 2014 ). Populations living within close proximity to coal mines have been shown to be at an increased risk of mortality and/or morbidity across numerous disease classifications including neoplasms, diseases of the circulatory, respiratory and genitourinary systems, metabolic diseases, diseases of the eye and skin, perinatal conditions, congenital and chromosomal abnormalities, and external causes of morbidity ( Cortes-Ramirez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%